2019
DOI: 10.1016/j.ebiom.2019.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Niacin analogue, 6-Aminonicotinamide, a novel inhibitor of hepatitis B virus replication and HBsAg production

Abstract: Background: Hepatitis B surface antigen (HBsAg) is one of the important clinical indexes for hepatitis B virus (HBV) infection diagnosis and sustained seroconversion of HBsAg is an indicator for functional cure. However, the level of HBsAg could not be reduced by interferons and nucleoside analogs effectively. Therefore, identification of a new drug targeting HBsAg is urgently needed. Methods: In this study, 6-AN was screened out from 1500 compounds due to its low cytotoxicity and high antiviral activity. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…In terms of antivirus effect, NA has been reported to inhibit HIV infection at a post-integration step of the viral life cycle [31]. When testing an analogue of NA, 6-amino-nicotinamide (6-AN), signi cant antiviral effect towards hepatitis B virus (HBV) through inhibition of cccDNA transcription to achieve the anti-HBV effect were seen [32]. These are consistent with our nding that NA also potently suppressed rotavirus replication.…”
Section: Discussionsupporting
confidence: 80%
“…In terms of antivirus effect, NA has been reported to inhibit HIV infection at a post-integration step of the viral life cycle [31]. When testing an analogue of NA, 6-amino-nicotinamide (6-AN), signi cant antiviral effect towards hepatitis B virus (HBV) through inhibition of cccDNA transcription to achieve the anti-HBV effect were seen [32]. These are consistent with our nding that NA also potently suppressed rotavirus replication.…”
Section: Discussionsupporting
confidence: 80%
“…Studies have confirmed antimycobacterial effect of NAM in patients infected with Mycobacterium tuberculosis [ 121 , 122 ], while immune-mediated elimination was reported for Staphylococcus aureus , including MRSA and other major human pathogens such as Klebsiella pneumoniae and Pseudomonas aeruginosa [ 123 ]. In addition, NAM and its analogues exhibited antiviral effect in patients with HIV [ 121 ] and hepatitis B [ 124 ]. The potential treatment with NAD + intermediates has been recognized recently for combating COVID-19 infection that currently lacks efficient therapeutic or preventive agents and represents a global concern for public health.…”
Section: Infection Treatment and Immunomodulatory Effectsmentioning
confidence: 99%
“…The viral surface antigen determines both functional and complete cure by its secretion levels in the serum. It also determines the host antiviral response, and its level in blood is positively correlated with intrahepatic HBV replication [27]. The sustained suppression of HBsAg secretion as a functional cure can be pursued or combined with conventional anti-HBV medicines or novel inhibitors of cccDNA formation to complete the treatment.…”
Section: Discussionmentioning
confidence: 99%